Analysis of the correlation between the dose exposure intensity and apatinib in advanced gastric cancer: a retrospective cohort study - Ma, Xiao; Gao, Lan; Che, Siying; Tao, Chaofeng (Frontiers in Oncology, 2025)
BackgroundApatinib is a small molecule anti-angiogenesis targeted drug that has demonstrated significant efficacy as a late-line treatment in advanced gastric cancer in phase 3 clinical trials. This study amid to evaluate the correlation between dose exposure intensity and efficacy and safety of apatinib in the treatment of advanced gastric cancer.MethodsWe conducted an observational, retrospective cohort study of patients with advanced gastric cancer who received apatinib targeted therapy in Beijing Friendship Hospital affiliated to Capital Medical University between June 1, 2018, and June 30, 2021. Dose exposure intensity (DEI) was defined as the product of dose and continuous medication time. Patients were assigned to high-dose exposure intensity (HDEI) and low-dose exposure intensity (LDEI) cohorts. The primary endpoint was progression-free survival (PFS), and the secondary endpoints were overall survival (OS) and safety. The relationship between HDEI and LDEI and clinical outcomes was analyzed by using the Kaplan-Meier curve and χ2 test.Results61 patients were enrolled and assigned into two retrospective cohorts. The median PFS (mPFS) were 6.50 months (95% confidence interval (CI) [4.80-9.20]) and 4.10 months (95% CI [3.70-5.20]), and the median OS (mOS) were 10.70 months (95% CI [9.20-18.50]) and 7.50 months (95% CI [6.80-9.30]) for the HDEI and LDEI cohorts, respectively. The mPFS were 5.85 months (95% CI [5.00-7.00]) and 4.60 months (95% CI [4.10-5.90]), and mOS were 9.60 months (95% CI [9.10-12.40]) and 7.60 months (95% CI [7.20-10.20]) the for the 250 mg cohort and 500 mg cohorts. The mPFS were 6.65 months (95% CI [5.90-9.20]) and 4.10 months (95% CI [3.90-5.20]), and the mOS were 11.20 months (95% CI [9.20-18.50]) and 7.60 months (95% CI [7.20-9.60])for the long medication time and short medication time cohorts, respectively. The most common TRAEs of any grade were hypertension, proteinuria, and neutrophil count decreased. The incidence of grade 3-4 adverse reactions in the 500 mg cohort was higher than the 250 mg cohort (P=0.0016).ConclusionThe efficacy of apatinib in advanced gastric cancer was significantly positively correlated with dose exposure intensity, and HDEI can prolong PFS and OS. Early application of low-dose apatinib (250 mg/d) can improve patients’ tolerability, and the adverse reactions are controllable.